Harnessing adrenergic blockade in stress-promoted TNBC in vitro and solid tumor in vivo: disrupting HIF-1α and GSK-3β/β-catenin driven resistance to doxorubicin - Attia, Yasmeen; Hakeem, Andrew; Samir, Rawda; Mohammed, Aya; Elsayed, Abdullrahman; Khallaf, Alaa; Essam, Eman; Amin, Hossameldeen; Abdullah, Sarah; Hikmat, Salwan; Hossam, Tarek; Mohamed, Ziad; et al. (Frontiers in Pharmacology, 2024)
Sympathetic activation triggered by chronic stress afflicting cancer survivors is an emerging modulator of tumorigenesis. Adrenergic blockade was previously associated with improving response to doxorubicin (DOX) in triple-negative breast cancer (TNBC), yet the precise underlying mechanisms remain obscure. The resilience of cancer stem cells (CSCs) during chemotherapy fosters resistance and relapse. Hypoxia-inducible factor-1α (HIF-1α) and β-catenin are intertwined transcriptional factors that enrich CSCs and evidence suggests that their expression could be modulated by systemic adrenergic signals. Herein, we aimed to explore the impact of adrenoreceptor blockade using carvedilol (CAR) on DOX and its potential to modulate CSCs overcoming chemoresistance. To achieve this aim, in vitro studies were conducted using adrenaline-preincubated MDA-MB-231 cells and in vivo studies using a chronic restraint stresspromoted solid tumor mouse model. Results revealed that adrenaline increased TNBC proliferation and induced a phenotypic switch reminiscent of CSCs evident by enhanced mammosphere formation. These results paralleled an increase in aldehyde dehydrogenase-1 (ALDH-1) and Nanog expression levels as well as HIF-1α and β-catenin upregulation. In vivo, larger tumor volumes were observed in mice under chronic stress compared to their unstressed counterparts. Adrenergic blockade using CAR, however, enhanced the impact DOX had on halting TNBC cell proliferation and tumor growth via enhanced apoptosis. CAR also curbed HIF-1α and β-catenin tumor levels subsequently suppressing ALDH-1 and SOX2. Our study unveils a central role for HIF-1α linking stress-induced sympathetic activation fueling CSC enrichment via the βcatenin pathway. It also highlights novel insights into CAR's capacity in reversing DOX chemoresistance in TNBC.